(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2019)
In these remarks I make the attempt to highlight a much pointed out in the media problem of the controversial behavior of Christian clergy, including the hierarchy of the Roman Catholic Church, as well the popes themselves. I call these sins. It is not – in my opinion – an abuse of the term, because the are a breach of norms and moral rules of that religion (and not only that). Those who commit them know about it and still they do not stop their practices – even despite the fact that one of them belongs to the sins “crying for hevean’s revenge.” Mostly those practices are being hidden before the eyes of others, and if that doesn’t succeed, they are being justified with circumstances they cannot control. It is however discussable how much these justifications are plausible.